GAMBARAN STRES PSIKOSOSIAL PADA PENDERITA HIPERTENSI PRIMER USIA DEWASA - Situmorang, Setiasima BR; Elita, Veny; Bayhakki, Bayhakki (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022DO - 10.24843/coping.2022.v10.i03.p15, 2022)
Adult age is a productive age that is vulnerable to various psychosocial stressors which are closely related to physical and psychological stress, causing hypertension problems. Primary hypertension in adulthood has a negative impact on physical and psychological. This study aims to determine the description of psychosocial stress in adults with primary hypertension. The method used by the researcher is quantitative with a descriptive research design carried out on 68 respondents with primary hypertension using purposive sampling technique. The measuring instrument used was a psychosocial stress questionnaire which was modified from the Holmes and Rahe Stress Inventory and DASS 42 questionnaire as well as literature review and data analysis using univariate analysis. The results showed that the majority of respondents experienced moderate psychosocial stress (52,9%). Respondents who experienced psychosocial stress based on household work with moderate psychosocial stress (53,3%). Based on physical illness, those with primary hypertension were not accompanied by other complaints with moderate psychosocial stress (54%). Based on interpersonal relationships that have close interpersonal relationships with mild psychosocial stress amounted to 52,9%. Psychosocial stress of adults with primary hypertension is in the category of moderate psychosocial stress.